APROXIMACIÓN AL ESTUDIO DEL RETABLO EN ANTEQUERA EN EL SIGLO XVIII - Camacho Martínez, Rosario; Romero Benítez, Jesús (Imafronte, 1989)
Though the Málaga baroque reredos panorama is scatterd and its reconstruction is quite a dficult task because many losses happened, the city of Antequera offers a set of specimens of speclal interest. During the XVIIIth century, important artists, like Antonio Mohedano and Bernardo Simón Pineda, appeared in this city. They both made a way to the Antequera retable in the eighteenth-century, this century being considered its golden age. Along this century, big machines were joined which evolved from a clearly baroque design to the classicistic models imposed by the rigour of the Academies. Therefore, the stages of the reredos in Antequera define models such as the so called castizos, a typical model in the first half of the XVIIIth century with twisted columns, a clear architectural scheme and a conspicuous manifestador [manifester] By the middle of the century, a rococo stage asserts itself coinciding with the acme of economy and population in Antequera; this stage has its most significant work in the main altarpiece of Carmen's church. The clear architectural scheme lost in favour of ornamentation and sculpture came back in the pseudoclassical stage, during the last third of the century; José M. de Aldehuela was its real initiator, the main retable of St. Zoilo's church being its most significant example. A last stage. the neoclassical one, offers a lesser interest and it gives rise to clearly neoclassical retables already in the XIXth century.